Clinical Observations and Occurrence of Complications following Heavy Silicone Oil Surgery. (14th April 2014) - Schwarzer, Hendrik; Mazinani, Babac; Plange, Niklas; Fuest, Matthias; Walter, Peter; Roessler, Gernot
Abstract : Purpose. To demonstrate development and complications in heavy silicone oil (HSO) surgery in 100 eyes following primary vitreoretinal surgery. Methods. 100 eyes were included in this retrospective study that underwent vitreoretinal surgery using HSO as endotamponade. Indication diagnoses were retinal detachments ( n = 76 ), complicated macular holes (MH) ( n = 20 ), and others ( n = 4 ) . HSO removal was performed after a mean period of 20.2 ± 19.0 weeks. In 18 eyes with poor functional prognosis the silicone oil remained permanently for stabilisation. Overall follow-up time was 35.9 ± 51.8 weeks. Results. The mean IOP before HSO surgery was 13.3 ± 5.6 mmHg and raised to an average maximum of 23.3 ± 8.5 mmHg postoperatively and decreased to 13.7 ± 7.2 mmHg after removal. Secondary IOP raise due to emulsification of the silicone oil endotamponade was seen in 29 eyes after 7.8 ± 4.5 weeks. Other complications being observed with HSO installed were persistent corneal erosion ( n = 3 ) and prolonged anterior chamber inflammation ( n = 29 ) . In 13 eyes recurrent retinal detachments occurred during followup. Conclusions. According to our analysis HSO surgery might deliver satisfying results in complicated cases of ophthalmological surgery. However, potential complications should always be taken into account when making the decision if to use and when to remove HSO in complicated retinal surgery.